Removal of Eroded Gastric Bands Using a Transgastric SILS Device - C. Spitali; K. De Vogelaere; G. Delvaux (Case Reports in Surgery)
Background. Laparoscopic adjustable gastric banding (LAGB) is a popular method for the treatment of morbid obesity. One of the most feared complications is gastric band erosion which occurs with a reported incidence of 0.3 to 14%. Intragastric migrated bands are best managed by endoscopic removal. Recent case studies reported successful endoscopic removal of intragastric migrated bands, but it is not always possible. We report our first experience with a transgastric removal of eroded bands using a Single Incision Laparoscopic Surgery (SILS) device. Methods. A patient who underwent gastric banding in the past (2007) presented with symptoms of epigastric pain and weight gain. Preoperative gastroscopy revealed stomach wall erosion with the gastric band partially (2/3) migrated into the gastric lumen. Attempts to remove the band by endoscopy were not successful. A laparoscopy was performed and multiple adhesions with evidence of inflammation was seen in the upper abdomen around the band. A SILS port was inserted through a 2 cm incision in the left hypochondrium with the internal ring of the port placed into the stomach through a small anterior gastrotomy. The band was cut in the stomach and removed. The anterior gastrotomy was closed. We had a perfect intragastric view of the gastric banding. Results. There were no intra- or postoperative complications. The patient was discharged on the fifth postoperative day on a gastric adapted diet. Conclusion. Removal of a gastric band after gastric erosion by SILS is feasible, safe, and effective. This is the first reported case of transgastric removal of eroded bands using an SILS device.